Corrigendum to “The experiences of Chinese colorectal cancer survivors in marital intimacy after ostomy creation: A qualitative study” [Belitung Nursing Journal, 2024; 10(2): 222-230] - Xixi Du; Suchira Chaiviboontham; Bualuang Sumdaengrit (Belitung Nursing Journal, 2026)
This corrigendum corrects clerical errors regarding the data collection timeline and interview methodology in the original article (DOI: https://doi.org/10.33546/bnj.3212). The authors confirm that these administrative corrections do not affect the methodology, data analysis, results, or conclusions of the original study and sincerely apologize for any inconvenience caused.